Differential Activation of Human Gingival Epithelial Cells and Monocytes by Porphyromonas gingivalis Fimbriae - Eskan, Mehmet A. (American Society for Microbiology, 2007)
Humans develop periodontitis in response to challenge by microbial dental plaque. Inflammation begins after perturbation of gingival epithelial cells by subgingival bacteria interacting through pattern-recognition receptors, including the Toll-like receptors (TLR). Porphyromonas gingivalis is a major periodontopathogen that interacts with epithelial cells through its cell surface fimbriae (FimA), leading to colonization and/or invasion. Previous work by our group has established membrane CD14 as an essential coreceptor for TLR2-mediated activation of transfected cell lines by P. gingivalis FimA. We have shown that gingival epithelial cells express TLR2 but not CD14 on their cell surfaces. We thus speculated that P. gingivalis FimA does not readily activate epithelial innate immune responses but rather functions to promote P. gingivalis colonization in the absence of a vigorous FimA-induced response. This hypothesis was verified by the findings that primary human gingival epithelial cells responded poorly to FimA in terms of interleukin (IL)-6, IL-8, granulocyte-macrophage colony-stimulating factor, and tumor necrosis factor alpha responses, in stark contrast to the marked response to other TLR2 agonists (Pam3Cys, FSL-1) that are not strictly dependent on CD14. On the other hand, CD14-expressing human primary monocytes responded with high levels of the same cytokines to both FimA and the control TLR2 agonists. The gingival epithelial cells failed to respond to FimA even in the presence of exogenously added soluble CD14. These data indicate that the gingival epithelial cell hyporesponsiveness to FimA is attributable to the lack of membrane-expressed but not soluble CD14. In conclusion, P. gingivalis FimA differentially activates human monocytes and epithelial cells, perhaps reflecting different tactics used by P. gingivalis when interacting with different host cell types or a host strategy to limit inflammation.